The complete chloroplast genome of Catalpa 'Bairihua', a hybrid variety with multi season flowering. Issue 3 (2nd July 2020) - Li, Wen-Qing; Lu, Yi-Zeng; Xie, Xiao-Man; Han, Yi; Wang, Ning; Sun, Tao; Liu, Li-Jiang; Wang, Yan; Zhuang, Zhen-Jie; Gao, Guang-Chen; Liu, Tao; Zhao, Li-Jun
Abstract: The complete chloroplast genome of Catalpa 'Bairihua' a hybrid variety with multi season flowering obtained from hybrid progeny of C. bungei ' Luoqiu Sihao' ( C. bungei '01' × C. bungei 'Changguo Qiu') and C. fargesii f. duclouxii was first sequenced with the Illumina HiSeq 2000 platform. Which was 158, 210 bp in length with a typical quadruple structure and contained a large single copy (LSC: 84, 928 bp) region and a small single copy (SSC: 12, 664 bp) region that were separated by a pair of inverted repeats (IRa, b: 30, 309 bp) region. The GC content of the whole chloroplast genome is 38.1%. A total of 130 genes was annotated in the complete chloroplast genome, including 85 protein-coding genes, 37 tRNA genes and 8rRNA genes. ML phylogenetic analysis by comparing with 39 chloroplast genomes of the Bignoniaceae indicated that Catalpa 'Bairihua' was close to Tecomaria capensis .